Difficultés De Transport International De Marchandises: Proposition D’un Cadre D’étude; Cas Du Maroc - Akoudad, Kawtar; Jawab, Fouad (European Scientific Journal, ESJ, 2018)
This paper focuses on developing an approach that identifies the problems of the international freight transport in Morocco. It also arranges these problems in order to have a reliable and detailed picture of the transport state. This problem was developed by approaching, in the first place, the importance and the role of the freight transport sector in Morocco. This sector, in addition to its vital importance for the economy, is of great social significance. In the second place, we deployed the quality management tools (the Ishikawa diagram and QQQOQCP tool) in order to identify, through literature, the problems of the international freight transport and understand the fundamentals of each difficulty. This analysis was corroborated by surveys that gathered information, reformulated dissatisfaction, and discerned weaknesses of the transport. In the last place and in order to prioritize the difficulties identified, we used the affinity diagram which allowed to model and group with clarity all the problems detected.